A conversation about critique as a signature pedagogy in the Arts and Humanities. (July 2017) - Motley, Phillip; Chick, Nancy L; Hipchen, Emily
This piece both previews and reviews the essays in this special section of Arts and Humanities in Higher Education. The three co-editors discuss the history of the project and what they learned at its conclusion.